IMPACT OF CSR DISCLOSURE AND ENVIRONMENTAL PERFORMANCE ON HEALTHCARE PROFITABILITY (IDX 2019-2022) - Antono, Gilang; Sudarno; Mulyono, Resha Dwi Ayu Pangesti (Bisma: Jurnal Bisnis dan Manajemen, 2025)
This research seeks to investigate and assess the impact of Corporate Social Responsibility (CSR) transparency and ecological performance on the financial returns of healthcare firms listed on the Indonesia Stock Exchange (IDX) over the 2019–2022 timeframe. A quantitative methodology was adopted, applying multiple linear regression techniques. The study population encompasses all IDX-listed healthcare entities, with the sample chosen through purposive sampling based on specific benchmarks, such as availability of annual reports, CSR disclosures, and involvement in the PROPER initiative, yielding 37 firm-year data points. Profitability is indicated by Return on Assets (ROA), CSR is evaluated via the CSR Disclosure Index referencing the 2016 GRI guidelines, and environmental performance is determined through PROPER scores. Results demonstrate that CSR and ecological performance jointly exert a meaningful influence on profitability. Individually, CSR shows a notable negative correlation with ROA, whereas environmental performance has a positive yet statistically insignificant impact. The conclusion suggests that despite CSR efforts enhancing corporate reputation, the substantial costs of implementation amid challenging times can dampen short-term profitability.